2021
DOI: 10.1002/1873-3468.14265
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxovanadates as new P‐glycoprotein inhibitors: insights into the mechanism of inhibition

Abstract: A promising strategy to overcome multidrug resistance is the use of inhibitors of ABC drug transporters. For this reason, we evaluated the polyoxovanadates (POVs) [V 10 O 28 ] 6-(V 10 ), [H 6 V 14 O 38 (PO 4 )] 5− (V 14 ), [V 15 O 36 Cl] 6− (V 15 ) and [V 18 O 42 I] 7− (V 18 ) as inhibitors of three major multidrug resistance-linked ABC transporters: P-glycoprotein (P-gp), ABCG2 and MRP1. All of the POVs selectively inhibited P-gp. V 10 and V 18 were the two most promising compounds, with IC 50 values of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…It is interesting to note that this is the first time that a protein structure bound to a V 15 cage is reported in the literature, although it has been demonstrated that [V 15 O 36 -(OH 2 )] 5À can inhibit the multidrug resistance-linked ABC transporter P-glycoprotein (P-gp) [5,54] and can act as indirect activator of a G protein-coupled receptor. [55] Here, we show at atomic level that the interaction of the V 15 cage with a protein occurs, possibly influencing the biological activity.…”
Section: Structure Bmentioning
confidence: 99%
“…It is interesting to note that this is the first time that a protein structure bound to a V 15 cage is reported in the literature, although it has been demonstrated that [V 15 O 36 -(OH 2 )] 5À can inhibit the multidrug resistance-linked ABC transporter P-glycoprotein (P-gp) [5,54] and can act as indirect activator of a G protein-coupled receptor. [55] Here, we show at atomic level that the interaction of the V 15 cage with a protein occurs, possibly influencing the biological activity.…”
Section: Structure Bmentioning
confidence: 99%
“…Cell responses for all MVPs were greater than those seen for cells treated with the human chorionic gonadotropin (hCG) hormone, which was used in reference [ 9 ]. Despite the promising biological effects described for V 15 , to the best of our knowledge, no evidence of toxicity (in vivo assays) was reported [ 2 , 3 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cell responses for all MVPs were greater than those seen for cells treated with the human chorionic gonadotropin (hCG) hormone, which was used in reference [9]. Despite the promising biological effects described for V15, to the best of our knowledge, no evidence of toxicity (in vivo assays) was reported [2,3,[29][30][31][32]. Although several POV compounds have demonstrated favorable biological properties, many aspects of the toxicity remain to be further investigated [33].…”
Section: Introductionmentioning
confidence: 99%